Classroom Techniques Used By The Teacher To Develop Students' English Reading Skills At Smp Muhammadiyah 10 Surakarta In 2015/2016 Academic Year: A Naturalistic Study - , Fitriasari; , Prof. Dr. Endang Fauziati, M.Hum; , Nur Hidayat, M.Pd (2016)
This study is aimed to describe classroom techniques used by the teacher to develop students' English reading skill at SMP Muhammadiyah 10 Surakarta. The type of this research is descriptive qualitative research especially naturalistic study. The method of collecting data in this research are observation, interview and document. The results of the research shows that there are some classroom techniques implemented by English teacher at SMP Muhammadiyah 10 Surakarta such as: reading aloud, translation sentence, silent reading, skimming and scanning, and question and answer. There are some classroom techniques used by the teacher and each classroom technique has purpose. The teacher has roles as controller, manager, facilitator, explainer, and motivator. The students have roles as subject of learning, object of learning, and monitor and evaluator of his own learning progress. There are some materials used by English teacher, such as: book, textbook, dictionary, another sources from internet as supplementary material. The roles of instructional materials are as a resource for presentation materials (spoken or written), as a reference source for learners on grammar, vocabulary, pronunciation, and so on, and as a resource of stimulation and ideas for classroom activities. The writer concludes that English teacher at SMP Muhammadiyah 10 Surakarta used several classroom techniques which can develop the students' English reading skill. Various classroom techniques can make the students more interested, active and not bored in teaching reading proses.